Естественная конвекция в замкнутой горизонтальной полости с волнистой стенкой - Павленко, Никита Сергеевич (Перспективы развития фундаментальных наук. Т. 3 : сборник научных трудов XIX Международной конференции студентов, аспирантов и молодых ученых, 26-29 апреля 2022 г.)
The work is devoted to the study of free convective heat transfer of a viscous incompressible fluid in a closed inclined cavity under conditions of a lower isothermally heated wavy wall and an upper isothermally cooled wall. The medium in the cavity is considered to be a heat-conducting liquid that satisfies the Boussinesq approximation. To describe the flow and heat transfer inside the cavity, unsteady Oberbeck-Boussinesq differential equations are used in dimensionless non-primitive variables "stream function - vorticity". To solve the formulated problem, the finite difference method of the second order accuracy has been used. The developed program code has been verified using different model problems. Effects of the amplitude and frequency of waves on the lower wall, as well as cavity inclination angle have been studied. The features of the development of convective structures inside the cavity are established, and the possibility of intensifying the heat transfer in a cavity with a wavy wall is shown.